2012
DOI: 10.1105/tpc.112.102608
|View full text |Cite
|
Sign up to set email alerts
|

The DUF59 Family Gene AE7 Acts in the Cytosolic Iron-Sulfur Cluster Assembly Pathway to Maintain Nuclear Genome Integrity in Arabidopsis

Abstract: Eukaryotic organisms have evolved a set of strategies to safeguard genome integrity, but the underlying mechanisms remain poorly understood. Here, we report that ASYMMETRIC LEAVES1/2 ENHANCER7 (AE7), an Arabidopsis thaliana gene encoding a protein in the evolutionarily conserved Domain of Unknown Function 59 family, participates in the cytosolic ironsulfur (Fe-S) cluster assembly (CIA) pathway to maintain genome integrity. The severe ae7-2 allele is embryo lethal, whereas plants with the weak ae7 (ae7-1) allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
139
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(145 citation statements)
references
References 72 publications
6
139
0
Order By: Relevance
“…It has been shown that AtTAH18, AtNBP35, AtNAR1, AtCIA1 and one of the AtCIA2 genes (named AE7) are each essential for embryo development (see table 1 and references). In contrast, Arabidopsis met18 knock-out mutants have no obvious phenotype [37].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that AtTAH18, AtNBP35, AtNAR1, AtCIA1 and one of the AtCIA2 genes (named AE7) are each essential for embryo development (see table 1 and references). In contrast, Arabidopsis met18 knock-out mutants have no obvious phenotype [37].…”
Section: Resultsmentioning
confidence: 99%
“…Although the precise molecular functions of these proteins remain to be determined, the formation of the complex and its biological function is conserved from yeast to humans and plants [37,48,49]. A universal phenotype of cia mutants is the loss of nuclear genome integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Although this domain has been identified in a wide array of proteins, and may have several functions, there is a family of ORFs that are part of a conserved chromosomal group of proteins predicted to be involved in iron-sulfur cluster metabolism (Almeida et al, 2005). Of the four published studies on proteins with DUF59 domain at the time of this submission, two have demonstrated the involvement of proteins with these domains in iron-sulfur cluster assembly (Chen et al, 2012;Luo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A small 105 aa protein, PG1777, has been shown to possess a domain of unknown function, DUF59 (www.ncbi.nlm.nih.gov), which has been identified in several bacteria and eukaryotes (Almeida et al, 2005;Chen et al, 2012;Luo et al, 2012). Although this domain has been identified in a wide array of proteins, and may have several functions, there is a family of ORFs that are part of a conserved chromosomal group of proteins predicted to be involved in iron-sulfur cluster metabolism (Almeida et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This assay has been used in Arabidopsis as a reliable method to quantify DNA repair kinetics in response to chemical and environmental agents that cause DNA damage (Luo et al, 2012;Nezames et al, 2012). The assay is prone to saturation and requires prior calibration of doses and the careful standardization of experimental conditions to maintain background DNA damage at a minimum (Collins et al, 2008).…”
Section: Flow Cytometrymentioning
confidence: 99%